Evaluation of antiurolithiatic effects of Parmelia perlata against calcium oxalate calculi in hyperoxaluric rats - Parveen Kumar Goyal & , Santosh Kumar Verma, Anil Kumar Sharma (Journal of Applied Pharmaceutical Science, 2018)
This study was aimed to evaluate the antiurolithiatic potential of Parmelia perlata extract (PPE) against calcium oxalate calculi in experimental rats. The drinking water containing 0.75% v/v Ethylene Glycol (EG) and 1% w/v Am-monium Chloride (AC) was used to induce hyperoxaluria in Wistar rats. Thirty-six rats divided into six groups (each containing six animals) were treated with vehicle (Normal control), EG + AC (Urolithiatic control), Cystone (Stan¬dard), and 100, 300 and 500 mg/kg, PPE (Tests). Administration of EG + AC produced significant hyperoxaluria and altered biochemical parameters of urine, serum and kidney tissue homogenates in lithiatic group. It caused glomerular atrophy, tubular deposition of oxalate crystals, altered renal architecture and impaired renal functions. PPE (100, 300 and 500 mg/kg, p.o., once daily for four weeks) significantly (p < 0.05) reversed the biochemical changes in urine, serum, and kidney tissue homogenates. It restored the normal renal functions and biochemical parameters like urinary pH, volume, creatinine clearance, BUN levels, uric acid concentrations and some inorganic parameters like oxalate, calcium, phosphorus contents, etc. The histopathological studies revealed that PPE restored the normal renal archi¬tecture in lithiatic rats. Conclusively, the experimental findings showed that PPE exhibited significant antiurolithiatic potential against calcium oxalate calculi in experimental rats.
Keywords: Parmelia perlata, Urolithiasis, Hyperoxaluria, Ethylene glycol, Oxalate calculi.